Frequency of Preterm Labour in Women Attending Delivery Suite of Civil Hospital, Karachi - Sami, Ayesha; Harim, Misbah; Ali, Nadia; Aneeta (Indus Journal of Bioscience Research, 2025)
Background: Preterm birth remains a widespread issue worldwide, ranking as a leading cause of neonatal mortality and a significant contributor to long-term health complications. Its multifactorial nature, involving both individual and environmental influences, poses challenges for effective prediction and prevention during antenatal care. While the global incidence of preterm births continues to rise, there is a notable lack of comprehensive data from developing nations like Pakistan. Methods: This cross-sectional study was conducted at Dr. Ruth K.M. Pfau Civil Hospital, Karachi, over six months (from July 01, 2024 to December 31, 2024), to determine the frequency and associated factors of preterm labor. A total of 213 women aged 18–45 years undergoing delivery were included using non-probability consecutive sampling. Data on demographics, clinical details, and BMI, categorized using Asian criteria, were collected. Preterm labor was diagnosed based on uterine contractions and cervical assessment. Data were analyzed using SPSS version 21, with stratification and chi-square/Fisher’s exact test applied to control effect modifiers. A p-value ≤ 0.05 was considered significant. Results provided insights into the prevalence and risk factors of preterm labor. Results: Among 213 participants, 26.29% experienced preterm labor with most preterm babies fell within the mild category (32–36 weeks, 60.7%) while moderate preterm (28–31 weeks, 26.8%) cases were second with extreme preterm (24–27 weeks, 12.5%) coming in as the least common. Chi-square tests revealed no significant relationships with residence, parity, or previous C-sections. Independent t-tests found no significant differences in continuous variables between groups. However, previous preterm delivery significantly predicted current preterm labor (p = 0.04). These findings suggest that preterm labor may be influenced by unmeasured or complex factors. Conclusion: This study found that previous preterm delivery was the only significant predictor of preterm labor, while factors such as age, BMI, residence, parity, and previous C-section showed no meaningful associations. These results emphasize the importance of focused interventions for women with a history of preterm birth to improve pregnancy outcomes.